Molecular Traits and Functional Analysis of the CLAVATA3/Endosperm Surrounding Region-Related Small Signaling Peptides in Three Species of Gossypium Genus - Lin, Huan; Wang, Wei; Chen, Xiugui; Sun, Zhenting; Han, Xiulan; Wang, Shuai; Li, Yan; Ye, Wuwei; Yin, Zujun (Frontiers in Plant Science, 2021)
The CLE (CLAVATA3/Endosperm Surrounding Region-related) small peptides are a group of C-terminally encoded and post-translationally modified signal molecules involved in regulating growth and development in various plants. However, the function and evolution of these peptides have so far remained elusive in cotton. In this study, 55, 56, and 86 CLE genes were identified in the Gossypium raimondii, Gossypium arboreum, and Gossypium hirsutum genomes, respectively, and all members were divided into seven groups. These groups were distinctly different in their protein characteristics, gene structures, conserved motifs and multiple sequence alignment. Whole genome or segmental duplications played a significant role in the expansion of the CLE family in cotton, and experienced purifying selection during the long evolutionary process in cotton. Cis-acting regulatory elements and transcript profiling revealed cotton CLE genes exist in different tissues, developmental stages, and in response to abiotic stresses. Protein properties, structure prediction, protein interaction network prediction of GhCLE2, GhCLE33.2, GhCLE28.1 peptides were respectively analyzed. In addition, the overexpression of GhCLE2, GhCLE33.2 or GhCLE28.1 in Arabidopsis, respectively, resulted in distinctive shrub-like dwarf plant, slightly purple leaves, large rosettes with large malformed leaves and a lack of reproductive growth. This study provides important insights into the evolution of cotton CLEs and delineates functional conservatism and divergence of CLE genes in cotton growth and development.